Alternative evaluations of economically optimal rations for broilers - Arraes, Ronaldo de Albuquerque e (1983)
In general, the main objective of a firm is to maximize profits, which implies cost minimization. This means that firms are always trying to improve technical and/or economic efficiency in production. The broiler industry is not an exception to this general rule as seen by the evolutionary improvement of efficiency in broiler production (Table 1-1). Yet, there are continuing problems that hinder improvements in efficiency of broiler production. The proportion of feed costs to total cost of broiler production has increased over time. Percentage distribu tion of production cost items, Table 1-2, demonstrate that feed has accounted for a major part of production costs. Hence, given a stable price for broilers, minimizing feed costs per pound of broiler is of primary concern to broiler growers seeking improvement in economic efficiency